IT Governance From Practitioners'Perspective: Sharing the Experience of a Malaysian University - Ajayi, Binyamin; Hussin, Husnayati (JATIT & Little Lion Scientific ( LLS), 2016)
The pervasive use of technology has led to organisations becoming more dependent on IT, hence the need for IT governance (ITG). ITG is viewed as IT behaviour deliberately designed and adopted by enterprises to enable them to achieve continuous organisation performance. Studies on how organisations achieve performance from ITG are relatively evolving. Thus frameworks on how universities govern their IT, if they exist, are scarce. This study attempts to explore how HEIs in Malaysia govern their IT to achieve performance based on empirical investigation of practitioners of a public university. Semi-structured interviews were conducted on three key university informants, namely, the Chief Information Officer; the IT Director and a management user, a Dean of functional unit. Interview's data were transcribed and thematic process of coding and theme generation was applied for analysis purposes. Based on this qualitative approach. The themes so generated were categorised under three capabilities of structure, process, and relations. Viewed from absorptive capacity of organisational learning theory, the findings show that when structures and processes are in place, the relationship between the IT and functional unit side of an organisation reflects the desired behaviour. The essence of such relationship is to attain effective IT governance, which will eventually lead to better organisation’s performance.